Computer-mediated discourse as a term and speech activity - Barkovich, Alexander A. (Journal of the Belarusian State University. Philology, 2025)
The term «discourse» has a wide set of overlapping meanings. One way or another, discourse is relevant not only in linguistics, sociology and philosophy, but also in informatics, web science, computer science and other scientific «applications» of communication. The adjustment of related term system demands the creation of a holistic picture of such an intangible aspect of communication as speech activity, intangible in the interdisciplinary sense, too. Moreover, the discursive paradigm absorbs step by step new appropriate conceptualisation – the informational one. In current communication a distinctive semiotic level is provided with artificial languages, forming a seemingly self-acting computer discourse. There even could be a reason to identify and describe it as artificial polycode discourse. But, generally, artificial languages – ill-fitted for the contextual semantics of natural language – do not have a full-featured set of communicational tools, as evidenced, for example, in machine translation practice. With that, the basic semiotic level – binary coding – does not represent any meaningful semantics beside the oppositional one. A computer initially needs more and more established artificial languages as mediums of natural-language semantics for binary coding, particularly. Finally, additional semiotic interfaces begin to ignore the semantics of the natural languages in which they have initially assisted. Then, there is another problem: the lack of the complete codification of speech practice, in communication of any kind. This is a general linguistic problem, which is a strong motive for the development of the «informationality» of meta-descriptions. Informational language, if invented, needs to adopt huge amounts of natural-language semantics via the low interpretational capacities of computer. In the meantime, the study of speech practice, mediated by computers, requires special attention to the appropriate terminological and conceptual interpretation. From the point of view of linguistics, «computer-mediated discourse» is quite correct term for characteristics of communication that occurs on the Internet and on separate computing devices. So, computer-mediated discourse is a speech activity in the communication mediated by computers. It is more precise than artificial-language discourse and computer discourse, for example. At least, it preserves the interdisciplinary nature of the denoted significate.